Combatting resistant enterococcal infections: a pharmacotherapy review. (13th June 2018) - Mercuro, Nicholas J; Davis, Susan L; Zervos, Marcus J; Herc, Erica S
ABSTRACT: Introduction : The role of enterococci in infectious diseases has evolved from a gut and urinary commensal to a major pathogen of concern. Few options exist for resistant enterococci, and appropriate use of the available agents is crucial. Areas covered : Herein, the authors discuss antibiotics with clinically useful activity against Enterococcus faecalis and E. faecium . The article specifically discusses: antibiotics active against enterococci and their mechanism of resistance, pharmacokinetic and pharmacodynamic principles, in vitro combinations, and clinical studies which focus on urinary tract, intra-abdominal, central nervous system, and bloodstream infections due to enterococci. Expert opinion : Aminopenicillins are preferred over all other agents when enterococci are susceptible and patients can tolerate them. Daptomycin and linezolid have demonstrated clinical efficacy against vancomycin-resistant enterococci (VRE). Synergistic combinations are often warranted in complex infections of high inoculum and biofilms while monotherapies are generally appropriate for uncomplicated infections. Although active against resistant enterococci, the pharmacokinetics, efficacy and safety of tigecycline and quinupristin/dalfopristin can problematical for severe infections. For cystitis, amoxicillin, nitrofurantoin, or fosfomycin are ideal. Recently, approved agents such as tedizolid and oritavancin have good in vitro activity against VRE but clinical studies against other resistant enterococci are lacking.